Postoperative Wound Irrigation Using Distilled Water in Preventing Surgical Site Infection in a Tertiary Hospital: A retrospective Cohort and Cost-effective Study - Jeo, Wifanto S.; Pratama, Dennis W.; Vanto, Yoni; Kekalih, Aria; Moenadjat, Yefta (The New Ropanasuri Journal of Surgery, 2020)
Background. The incidence of surgical site infections (SSIs) is reducing following the global campaign that requires all the stakeholder involvement. However, of all hospital-acquired infection prevention programs, wound irrigation is hard to be implemented in our hospital. There is a belief that the wound irrigation procedure leading to the spreading of infection. In contrast, the use of antiseptic and topical antibiotic, as well as systemic antibiotic, is uncontrolled high. Thus, we run a cost-effective study of wound irrigation to change the practice. Method. We carried out a prospective cohort study comparing wound irrigation and the standard protocol in wound care in those underwent median laparotomy during the period of January to July 2018. A total of 80 subjects enrolled in this study, which divided into two groups, 40 for each group. The first group was those treated using antiseptics (povidone-iodine) and antibiotic contained paraffin tulle, while the second group was those treated using irrigation. This study performed in the digestive surgery division, which initiated irrigation protocol for wound irrigation. Stitch specimen taken for bacterial culture proceeded on 7th day postoperative and clinical signs of infection following CDC criteria was observed then statistically analyzed. The committee of ethics Faculty of Medicine Universitas Indonesia approved the study. Results. The bacterial culture showed no significant difference (p = 0.82) between the two groups. Clinical signs are showing no significant difference between the two groups (p = 1.00). In the cost perspective, the application of wound irrigation saving IDR 57,500,00 or four USD per subject. Conclusion. Wound irrigation using distilled water efficiently prevent SSIs.